The influence of large convective eddies on the surface-layer turbulence - Zilitinkevich, Sergej S.; Hunt, J. C.R.; Esau, I. N.; Grachev, A. A.; Lalas, D. P.; Akylas, Evangelos; Tombrou, M.; Fairall, C. W.; Fernando, H. J.S.; Baklanov, A. A.; Joffre, S. M. (My University, 2006)
Close to the surface large coherent eddies consisting of plumes and downdraughts cause convergent winds blowing towards the plume axes, which in turn cause wind shears and generation of turbulence. This mechanism strongly enhances the convective heat/mass transfer at the surface and, in contrast to the classical formulation, implies an important role of the surface roughness, In this context we introduce the stability-dependence of the roughness length. The latter is important over very rough surfaces, when the height of the roughness elements becomes comparable with the large-eddy Monin-Obukhov length. A consistent theoretical model covering convective regimes over all types of natural surfaces, from the smooth still sea to the very rough city of Athens, is developed; it is also comprehensively validated against data from measurements at different sites and also through the convective boundary layer. Good correspondence between model results, field observations and large-eddy simulation is achieved over a wide range of surface roughness lengths and convective boundary-layer heights. © Royal Meteorological Society, 2006.
Keywords: Convection; Heat and mass transfer; Minimum friction velocity; Semi-organized structures; Surface fluxes